2002
DOI: 10.1128/jb.184.6.1571-1577.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Acetoacetyl Coenzyme A Synthetase-Dependent Pathway for Utilization of l -(+)-3-Hydroxybutyrate in Sinorhizobium meliloti

Abstract: D-(؊)-3-Hydroxybutyrate (DHB), the immediate depolymerization product of the intracellular carbon store poly-3-hydroxybutyrate (PHB), is oxidized by the enzyme 3-hydroxybutyrate dehydrogenase to acetoacetate (AA) in the PHB degradation pathway. Externally supplied DHB can serve as a sole source of carbon and energy to support the growth of Sinorhizobium meliloti. In contrast, wild-type S. meliloti is not able to utilize the L-(؉) isomer of 3-hydroxybutyrate (LHB) as a sole source of carbon and energy. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…We have previously shown that the presence of multiple copies of the S. meliloti acsA2 gene could suppress the 3-hydroxybutyrate utilization phenotype of the S. meliloti bdhA mutant [26]. To test whether a similar phenomenon operates in NGR234, plasmid pGQ105 [27], bearing the S. meliloti acsA2 gene on an IncP plasmid, was introduced into NGRPA2.…”
Section: Suppression Of the Ngr234 Bdha Phenotype By Multiple Copies mentioning
confidence: 99%
“…We have previously shown that the presence of multiple copies of the S. meliloti acsA2 gene could suppress the 3-hydroxybutyrate utilization phenotype of the S. meliloti bdhA mutant [26]. To test whether a similar phenomenon operates in NGR234, plasmid pGQ105 [27], bearing the S. meliloti acsA2 gene on an IncP plasmid, was introduced into NGRPA2.…”
Section: Suppression Of the Ngr234 Bdha Phenotype By Multiple Copies mentioning
confidence: 99%
“…Ketone bodies are a vital alternative metabolic fuel source for all the domains of life, eukarya, bacteria, and archaea (Aneja et al, 2002; Cahill GF Jr, 2006; Krishnakumar et al, 2008). Ketone body metabolism in humans has been leveraged to fuel the brain during episodic periods of nutrient deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism of ketone bodies is conserved among eukarya, bacteria, and archaea (8,33,113). Ketone bodies are synthesized in liver from acetyl-CoA derived primarily from fatty acid oxidation and are transported to extrahepatic tissues for terminal oxidation during physiological states characterized by limited carbohydrate and surplus fatty acid availability [reviewed in (137,167); Fig.…”
Section: Introductionmentioning
confidence: 99%